Primal. The complete third season [videorecording (DVD)] - Tartakovsky, Genndy, 1970- (Warner Bros., 2026)
"Continuing the combination of artistry and pulse-pounding action that made the first two seasons instant classics, the third season of Genndy Tartakovsky's Primal opens with a shocking twist that resurrects Spear in a new form -- stripped of memory and humanity -- and forces him to roam a brutal, untamed world as a shadow of his former self. As Spear battles savage landscapes and deadly foes, faint echoes of his past begin to stir, leading him toward an emotional and explosive reunion that will test the limits of survival."--Disc container.